Dva Fedora . The Two Fedors - Khutsiyev, Marlen (Odesskaia Kinostudia, 1958)
The first post-WW II days. On his way from the front officer Fedor meets a little orphan boy who is also called Fedor and adopts him. The two start a new life together, but a young boy has to learn to get along with the 'older' Fedor's wife too.